Echoes of Contemporary Indian Francophone Literature - Diana Mistreanu (Ksiegarnia Akademicka Publishing, 2019)
This article analyzes Shumona Sinha’s first novel, Fenêtre sur l’abîme (Window to the Abyss, 2008) from a cognitive perspective. As the narrator, a young Bengali woman named Madhuban, is struggling to make sense of her existence, past events and present sensations, as well as nightmares and memories unfold in an accelerating rhythm, questioning the impact of her life experience upon her mental health. Drawing on Alan Palmer’s typology of fictional minds, the aim of this work is to provide some preliminary remarks on the textual representation of the narrator’s mind, depicted on the verge of a mental breakdown triggered the by physical and emotional abuse she was subjected to by her family in Calcutta, and reinforced by her emigration to Paris.